2011
DOI: 10.3233/jvr-2011-0556
|View full text |Cite
|
Sign up to set email alerts
|

Supported versus sheltered employment: Cumulative costs, hours worked, and wages earned

Abstract: This paper examined the costs of services received and outcomes obtained by 112 supported and sheltered employees. Overall, sheltered employees received services for longer periods (M = 72.92 months v. 44.91 months) as well as worked more hours per month (M = 65.68 v. 58.95) than supported employees. However, supported employees on average generated fewer cumulative costs (M = $22.406 v. $45.840) and earned more wages per month

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 5 publications
(9 reference statements)
1
5
0
1
Order By: Relevance
“…Its termed 'hybrid' because they do not conform to the full criteria of sheltered employment. This correlates with the evidence that although service users of other supported-employment programs earned more wages, service users of sheltered employment (hybrid model) actually worked for a longer duration of time (Cimera, 2011). An RCT in the same study site reported that although the IPS program produced significantly higher competitive employment rates than that of the hybrid model, the hybrid model was better in other vocational outcomes in terms of likelihood of employment and higher number of employment days in any type of paid employment (Chua & Abu Bakar, 2015).…”
supporting
confidence: 74%
“…Its termed 'hybrid' because they do not conform to the full criteria of sheltered employment. This correlates with the evidence that although service users of other supported-employment programs earned more wages, service users of sheltered employment (hybrid model) actually worked for a longer duration of time (Cimera, 2011). An RCT in the same study site reported that although the IPS program produced significantly higher competitive employment rates than that of the hybrid model, the hybrid model was better in other vocational outcomes in terms of likelihood of employment and higher number of employment days in any type of paid employment (Chua & Abu Bakar, 2015).…”
supporting
confidence: 74%
“…This corroborates many other studies (cf. Cimera, 2011;Kregel et al, 1989;Thompson et al, 1992) and adds credence to the notion that supported employment is cost-efficient from the worker's perspective, even when the individual has significant and multiple disabilities.…”
Section: Discussionmentioning
confidence: 81%
“…Integrated employment for people with disabilities translates to improved quality of life (Bayer, Brown, Akandi, & Rapley, 2010), improved self-esteem (Petrovski, 1997;Wehman, Inge, Revell, & Brooke, 2007), and improved wages (Cimera, 2012;Cimera & Burgess, 2011). For example, Cimera (2012) reviewed the literature on the economics of supported employment and found that wages of individuals with disabilities had increased by 31.2% since the 1980s while wages of sheltered workshop employees had decreased by 40.6% during the same period.…”
Section: Introductionmentioning
confidence: 99%